Gastrocytoprotective properties of cryopreserved placenta extract in combined action of low temperatures and inhibition of cyclooxygenase - Гладких, Ф.В. (Acta Facultatis Medicae Naissensis. 2022. № 39(1). Р. 48–56., 2022)
Non-steroidal anti-inflammatory drugs (NSAIDs) are rank first among the world's effective anti-inflammatory and analgesic drugs with anticipated side effects. That is why prevention of development of adverse reactions associated with NSAIDs, in particular, of those related to their ulcerogenicity, remains a serious global problem. Purpose – to characterize the mechanisms of gastrocytoprotective activity of cryopreserved placenta in combined action of low temperatures and diclofenac sodium. Material and methods. The study was performed on 42 male rats weighing 200–220 g. Acute diclofenac sodium-induced gastropathy was reproduced by a single injection of the latter in rats at a dose of 50 mg/kg. The content of malonic dialdehyde, catalase activity, prostaglandin synthase activity and the content of nitrogen monoxide metabolites in homogenates of gastric mucosa were determined by spectrophotometric method. Results and discussion. The study showed that prophylactic administration of placental cryoextract in rats with diclofenac sodium-induced gastropathy is associated with increased activity of antioxidant system in gastric mucosa as demonstrated by an elevated catalase activity by 40.0% as compared with control rats. Modulation of antioxidant-prooxidant homeostasis is believed to be one of the principal mechanisms of gastrocytoprotective action in combined action of low temperatures and cryoextract of the placenta. This is shown by a statistically significant (p<0.05) 2.2-fold increase of antioxidant-prooxidant index in the study group as compared with rats with diclofenac sodium-induced gastropathy. Administration of placental cryoextract was found to increase prostaglandin synthase activity in rats with diclofenac sodium-induced gastropathy 2.0-fold as compared with control rats, which would reduce iatrogenic prostaglandin deficiency in gastric mucosa. Also, the combined action of low temperatures and of placenta cryoextract was associated with a statistically significant (p <0.05) increase in the level of metabolites of nitrogen monoxide (by 70.1%) as compared with rats with diclofenac sodium-induced gastropathy. Conclusions. Modulation of prooxidant-antioxidant homeostasis in gastric mucosa and increase of contents of nitrogen monoxide metabolites and prostaglandin synthase activity are the leading mechanisms of gastroprotective activity of cryopreserved placental extract under diclofenac sodium-induced urea.
Hladkykh F. V. Gastrocytoprotective properties of cryopreserved placenta extract in combined action of low temperatures and inhibition of cyclooxygenase. Acta Facultatis Medicae Naissensis. 2022. № 39(1). Р. 48–56. DOI: https://doi.org/10.5937/afmnai39-33036
Keywords: Gastrocytoprotective properties; cryopreserved placenta extract; low temperature; cyclooxygenase; nonsteroidal anti-inflammatory drugs